Development of Al alloy composites by powder metallurgy routes - Jiang, X (2014)
Particulate reinforced Al alloy composites (AlMCs) are recognized as important structural materials due to their lightweight, high modulus and strength and high wear resistance. In order to understand the effect of matrix, reinforcement and secondary processing techniques on the microstructure development and mechanical properties of AlMCs produced by powder metallurgy routes, Al alloy composites reinforced with three types of reinforcements by different secondary processing techniques have been produced and examined. Fabrication of Al or 6061Al alloy based composites reinforced with nano-sized SiC particles (~500nm), micro-sized (<25µm) quasicrystalline alloy particles (hereinafter referred to as “NQX”) and micro-sized Nb particles (~130µm) has been carried out by powder metallurgy routes followed by extrusion or cold rolling. After extrusion, a homogeneous distribution of secondary particles has been obtained with rare interfacial reaction products. The 6061Al/SiC composites exhibit superior mechanical properties than either monolithic alloys or composites reinforced with micro-sized particles with retained ductility while the 6061Al/NQX and 6061Al/Nb composites show limited improvement in tensile strength mainly due to their reinforcement size and poor interfacial bonding. After cold rolling, the evolution in microstructure, texture and strength has been analysed. A typical near β fibre texture with highest intensities near Copper and Brass orientations has been developed for 6061Al/NQX and 6061Al/Nb composites. For 6061Al/SiC composites, a randomized texture with very small grains has achieved due to the presence of the non-deformable SiC particles. Mechanical property tests including microhardness, three-point bending tests and tensile tests have been carried out on cold rolled samples and the results exhibit some level of improvement when compared with as-extruded samples due to work hardening. Finally, the work moves on to the general discussion based on the previous result chapters. The microstructural development related to reinforcement, matrix and interfacial areas during extrusion and cold rolling has been summarised and the correlation between microstructure and mechanical properties has been discussed. The thesis provides a thorough understanding of AlMCs produced by powder metallurgy routes in terms of matrix, reinforcement and processing techniques. It can provide reference to the future development of AlMCs for high strength applications.